The Influence of Content Marketing and Electronic Word of Mouth on Customer Retention at Jatiroso Catering - Sa'diyah, Khikmatus; Mubarokah, Mubarokah; Wijayati, Prasmita Dian (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research aims to analyze the effect of content marketing (X1) and electronic word of mouth (eWOM) on customer retention (Y) at Jatiroso Catering. A questionnaire with 98 respondents chosen using non-probability sampling methods was used to gather primary data, namely purposive sampling and voluntary sampling. Through the use of the Smart PLS 4 application, the study methodology employs Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. According to the study's findings, content marketing significantly and favorably affects 39.9% of customers' retention rates. However, with a 27.4% contribution, eWOM also has a favorable and noteworthy impact on customer retention. These findings confirm that both variables are statistically demonstrated to have a major impact in raising customer retention at Jatiroso Catering.